PO128 Infusion-related reactions with ocrelizumab in rms and ppms. (1st December 2017) - Seze, Jérôme de; Bar-Or, Amit; Giovannoni, Gavin; Hemmer, Bernhard; Kappos, Ludwig; Lublin, Fred; Wolinsky, Jerry; Li, Carrie; Mairon, Nicole; Hauser, Stephen L
Abstract : Background: Infusion-related reactions (IRRs) have been observed with ocrelizumab treatment. Objective: To evaluate the pattern of IRRs in studies of ocrelizumab in relapsing (OPERA I/II [NCT01247324 /NCT01412333]) and primary progressive (ORATORIO [NCT01194570 ]) multiple sclerosis. Methods: During the 96 week OPERA studies, patients received ocrelizumab 600 mg via intravenous (IV) infusion every 24 weeks or subcutaneous interferon beta-1a (IFNβ−1a) 44 µg three-times weekly. In ORATORIO, patients received ocrelizumab 600 mg IV given as two 300 mg infusions 14 days apart or matching placebo every 24 weeks for ≥120 weeks. Patients were pretreated with IV methylprednisolone 100 mg or blinded equivalent; analgesics/antipyretics and antihistamines were recommended. Results: Safety analyses included patients from OPERA I/II (ocrelizumab, n=825; IFNβ−1a, n=826) and ORATORIO (ocrelizumab, n=486; placebo, n=239). Infusion-related reactions were more common with ocrelizumab versus comparator in OPERA I/II (34.3% vs 9.7% with IFNβ−1a) and ORATORIO (39.9% vs 25.5% with placebo), and were most frequent with the first infusion, decreasing thereafter. The majority of IRRs were mild to moderate in severity and most commonly included pruritus, rash, throat irritation and flushing. Conclusions: The most common adverse event in these studies was IRRs, which were mostly mild to moderate in severity and decreased in incidence after the first infusion.